Multimodal continuous emotion analysis - Zhang, Su (Nanyang Technological University, 2023)
Emotion recognition is an increasingly popular research topic in various fields, including human-computer interaction and affective computing. Continuous emotion recognition (CER), a sub-task in this area, focuses on performing sequence-to-sequence regression on the provided emotion cues, as opposed to other research topics such as sequence-to-category emotion classification.